1997
DOI: 10.1128/aac.41.1.196
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of fluconazole- and amphotericin B-resistant Candida albicans from blood of two patients with leukemia

Abstract: Infections with fluconazole-resistant Candida albicans isolate have rarely been described in clinical settings other than oropharyngeal candidiasis in patients with late-stage AIDS. We report on two patients with leukemia who developed fungemia caused by fluconazole-resistant C. albicans after receiving fluconazole prophylaxis (400 mg/day) and empiric amphotericin B therapy (0.5 mg/kg of body weight per day). The fluconazole MICs for the isolates were > or = 64 micrograms/ml, and the isolates were resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(69 citation statements)
references
References 15 publications
0
67
0
2
Order By: Relevance
“…Similarly, mutations in ERG11, which encodes sterol 14a-demethylase, can affect binding of azoles to the enzyme, resulting in increased drug resistance of the cells (Kelly et al, 1999a(Kelly et al, , 1999bLamb et al, 2000). Increased expression of ERG11 can also contribute to azole resistance (Du et al, 2004;Marichal et al, 1997), and alterations in the sterol biosynthesis pathway that bypass the accumulation of toxic sterols result in azole-resistant Candida strains (Kelly et al, 1994;Nolte et al, 1997;Pinjon et al, 2003). Such mutations may cause cross-resistance to several drugs with the same mode of action.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, mutations in ERG11, which encodes sterol 14a-demethylase, can affect binding of azoles to the enzyme, resulting in increased drug resistance of the cells (Kelly et al, 1999a(Kelly et al, , 1999bLamb et al, 2000). Increased expression of ERG11 can also contribute to azole resistance (Du et al, 2004;Marichal et al, 1997), and alterations in the sterol biosynthesis pathway that bypass the accumulation of toxic sterols result in azole-resistant Candida strains (Kelly et al, 1994;Nolte et al, 1997;Pinjon et al, 2003). Such mutations may cause cross-resistance to several drugs with the same mode of action.…”
Section: Introductionmentioning
confidence: 96%
“…Mutations that cause defects in the uptake of flucytosine or in its intracellular conversion are a frequent cause of resistance to this drug (Dodgson et al, 2004;Florent et al, 2009;Hope et al, 2004;Noel et al, 2003;Papon et al, 2007). A decrease in the membrane ergosterol content can lead to reduced polyene susceptibility (Kelly et al, 1994Nolte et al, 1997;Pinjon et al, 2003;Vandeputte et al, 2007;Young et al, 2003), although this type of resistance is rarely observed and of minor importance. Mutations in the FKS1 gene, encoding a subunit of the b-1,3-glucan synthase complex, result in resistance to echinocandin drugs (Perlin, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Phenotypically stable resistance to azole antifungal agents in C. albicans can result from mutations or increased expression of genes involved in the ergosterol synthesis pathway (including the target enzyme 14-a demethylase), and increased expression of ATP-binding cassette (ABC) transporter and major facilitator efflux pumps . Moreover, the resistance can be rapidly developed in C. albicans after short exposures to the drug, both in vitro (Calvet et al, 1997) and in vivo (Marr et al, 1997;Nolte et al, 1997), notably in a strain of C. albicans that caused disseminated infection in a patient after bone marrow transplantation (BMT) (Marr et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…They further concluded that disruption of ergosterol biosynthesis in general would confer resistance to AmB. Similarly, examination of AmB-resistant, clinical C. albicans isolates indicated that these cells exhibited alternate sterol composition in their cell membranes consistent with ERG3 disruption [2,3].…”
Section: Resistance To Polyenesmentioning
confidence: 94%